Analysis of Specialization in Agricultural Products After WTO Membership: A Review for Türkiye and Mercosur Countries Agricultural Trade Relation - Elif Tuğçe Bozduman (Turkish Journal of Agriculture: Food Science and Technology)
The increase in the volume of foreign trade between Türkiye and MERCOSUR countries in recent years has an important potential. The fact that these countries are economically similar further increases the mutual foreign trade potential. These trade relations are important in terms of economic cooperation and are expected to strengthen the economic interests of countries over time. Both Türkiye and MERCOSUR countries have a high potential in terms of production and foreign trade in agricultural and livestock products. Of course, the fact that countries are members of the World Trade Organization has increased free foreign trade in these sectors. Therefore, in this study, the level of foreign trade specialization in the agriculture and livestock sector after Türkiye and MERCOSUR countries became a member of the World Trade Organization was analysed. In this study covering the years 1995-2022; Net Trade, Export-Import Ratio, Lafay and Michaely indices were used. The findings show that the highest specialization is in Argentina and the lowest in Paraguay. In addition, Türkiye and Brazil have an advantage in numerically similar product groups. Türkiye needs to increase productivity in agriculture to increase the level of specialization in foreign trade.